Dopamine Detox sebagai Praktik Zuhud Era Modern dalam Upaya Mengatasi Dampak Negatif Teknologi - Ariq, Naufal (Jurnal Riset Agama, 2024)
This research aims to explore the potential of dopamine detox as a modern approach to managing technology addiction through the application of the concept of zuhud. In the digital age, excessive use of technology has triggered addiction, which negatively impacts mental health, productivity and life balance. Using a qualitative-descriptive approach, this study collected data through literature review, in-depth interviews, and observations of individuals undergoing dopamine detox practices. The results show that dopamine detox is effective in helping individuals reduce excessive stimulation from technology, improve self-control, and focus attention on things that are more meaningful and useful. This practice is also in line with the values of zuhud, which teaches life balance through the avoidance of excessive things. This study concludes that dopamine detox can be adopted as a strategy to overcome technology addiction, support mental health, and promote the value of spirituality in modern life.